The integration of the 4p's towards the development of Perwira Habib Bank (M) Berhad / Rohaida Suleman - Suleman, Rohaida (1992)
Marketing is the business function that identifies unfulfilled needs and wants, defines and measures their magnitude, determines which target markets the organization can best serve, decides on appropriate products, services and programs to serve these markets and call upon everyone in the organization to "think and serve the customer". Marketing must not be seen narrowly as the task of finding clever ways to sell the company's product. Authentic marketing is not the art of selling what you make but knowing what to make. Knowing to sell is no longer adequate in this age of competitive retail banking as all banks provides "me-too" products. PHB as a medium sized bank have limited resources to serve all segments and realizing that the Bank only concentrates on niche marketing by capturing "a slice of a big pie", small but profitable. Specialization is more profitable than to venture into the big market with limited resources. This study is regarding PHB's marketing mix - that are product, price, promotion and place in analyzing and understanding the integration of the 4P's towards the development of PHB. Before any selling could be carried out, the Bank have to understand the 4P's first. By understanding these, PHB can develop effective strategies to better serve customers and develop products to suit their needs and wants.